Overcoming Stunting with A Healthy Papua Kitchen in Sentani, Jayapura District - Tiyan Febriyani Lestari; Hasnia Hasnia; Nasrianti Nasrianti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stunting is a condition in which toddlers experience growth failure due to impaired nutrient absorption. The impact of stunting is brain disorders, intelligence, metabolic disorders in the body, heart, diabetes, stroke and disability in old age. So it will affect the quality of human resources, productivity, and national competitiveness in Indonesia. Objective to overcome stunting by utilizing Papua's natural resources such as sago and Sentani Lake snakehead fish which will be processed into cookies, as well as monitoring the growth and development of toddlers. Experiment with completely randomized design and Quasy Experiment approach one Group Pretest and Posttest with a sample 14 toddlers with accidental sampling. this study was divided into 4 stages; manufacturing cookies, organoleptic test and content analysis cookies after which experimental test. There is an effect of giving sago cookies and snakehead fish on changes in toddler weight, with a significance value of 0.000 (<0.05) and giving cookies with height measurement obtained a significance value of 0.189 (>0.05). There is an effect of giving sago cookies and snakehead fish on weight gain and there is no effect of giving sago cookies and snakehead fish on changes in height.